Application of Hotelling T2 Control Diagram to Analyze Drinking Water Quality Control at Perumda Tirtauli Pematang Siantar City - Sari, Elviana; Widyasari, Rina (Universitas Wiralodra, 2024)
Water is the most important element in supporting human life and other living creatures, where the role of water cannot be replaced by other elements. Various human activities always require large amounts of water to meet their daily needs. People really need good water quality because it has a big impact on health. However, many people complain that the water quality at PDAM Tirtauli Pematang Siantar, the water production they get is less than satisfactory, meaning that the water production at PDAM Tirtauli Pematang Siantar is of poor quality because they have not been able to distribute water production in accordance with the wishes of the community.This study aims to determine the process of controlling the quality of clean water production at PDAM Tirtauli Pematang Siantar with the Hotelling T2 control diagram. T2 hoteling is a multivariate analysis technique used to compare two groups of samples using an average vector, each consisting of two or more variates. The data used in this study is drinking water production data during June-July 2022. Based on the analysis that has been done, it is found that on the T2 hoteling control map, the results show that the drinking water production process at PerumdaTirtauli, Pematang Siantar city is statistically controlled because there are no points that cross the upper control limit or the lower control limit on the T2 Hotelling control map.